Marketing ethics and the techniques of neutralization - Vitell, Scott J. (Journal of business ethics, 1987)
The need for conceptual work in marketing ethics is addressed by examining the five techniques of neutralization as a means for partially explaining “unethical” behaviors by marketing practitioners. These techniques are often used by individuals to lessen the possible impact of norm-violating behaviors upon their self-concept and their social relationships. Borrowed from the social disorganization and deviance literature, the five techniques of neutralization are: (1) denial of responsibility, (2) denial of injury, (3) denial of victim, (4) condemning the condemners and (5) appeal to higher loyalties. Examples of marketing professionals using each of the five techniques are given, and a conceptual model linking the techniques of neutralization with “unethical” behavior is presented. Finally, relevant research questions are offered for consideration.